The Transboundary Sundarban Mangroves: A Struggling Ecosystem - Chandan Surabhi Das; Pritam Sarkar (Surviving Sundarbans: Tragedy and Hope, Edition 1, 2025)
The Sundarban region is one of the world’s most vulnerable coastal ecosystems, facing significant threats from logging, overexploitation, and climate change, including intensified storms, and rising sea levels. Despite being the most productive ecosystem on the earth, the mangrove forests, which support diverse flora and fauna and provide essential services to coastal communities, have declined significantly over the past two centuries. The Sundarban contain 45 mangrove species and 21 species of under-canopy vegetation which experienced an annual degradation rate of about 0.114% from 2005 to 2023. Soil nitrogen content ranges from 0.04% to 0.08%, with high levels of water-soluble and exchangeable magnesium, calcium, and potassium in the Oligohaline zone. The ongoing conflict between resource exploitation and local livelihoods in forested areas underscores the vital role of vegetation in maintaining ecosystems and biodiversity. Typically, there is an inverse correlation between the well-being of local communities and the health of forest ecosystems. As these communities seek to meet their economic needs, pressure on forest resources increases, leading to environmental degradation and reduced biodiversity.